Design And Construction Of Liquid Level Measurement System - Ab Hadi, Nik Azran; Mohd Annuar, Khalil Azha; Saadon, Intan Mastura; Harun, Mohamad Haniff (Akademia Baru, 2015)
Industrial tank system play important role in industrial application such as in food processing, pharmaceutical industry, chemical industry, water purification system and many more. Today we can see a lot of varieties in different level measurement technologies on the market like ultrasonic level sensor, capacitance level sensor, microwave sensor, and others. One of the frequent used industrial tank systems is couple tank system. The main interest of the use PID is to ensure the supply of liquid is at constant rate. This paper will discuss on the system based on microcontroller unit design to measure and control liquid level accurately to improve the efficiency of motor pumping unit. To developed this system, ATMEGA32 starter kit board is use to control pumping unit (motor), continuous fluid level sensor to measure the liquid level with LED display circuit, and temperature sensor is used to measure the current temperature of liquid inside tank. The system software is written in C language, interrupt routines are used to record and deal with the time data to count the liquid level accurately. This system supposedly can measure the water level up to 25cm and work at 5V supply voltage range.